Maintenance dose conversion between oral risperidone and paliperidone palmitate 1 month: Practical guidance based on pharmacokinetic simulations. Issue 6 (30th April 2018) - Russu, Alberto; Kern Sliwa, Jennifer; Ravenstijn, Paulien; Singh, Arun; Mathews, Maju; Kim, Edward; Gopal, Srihari
Summary: Aim: We assessed the dosage strengths of paliperidone palmitate 1‐month (PP1M) long‐acting injectable resulting in similar steady‐state (SS) exposures to the dosage strengths of oral risperidone using pharmacokinetic (PK) simulations. Methods: Population PK simulations of SS PK were performed using the PK models of oral risperidone and PP1M. The concentrations of active moiety (risperidone + paliperidone) from risperidone were compared to paliperidone concentrations resulting from PP1M administration. Similarity was assessed via graphical evaluation of median and 90% prediction intervals of SS PK profiles over 28 days. Results: Oral risperidone doses of 1, 2, 3, 4, and 6 mg/d are expected to result in similar SS PK as PP1M doses of 25, 50, 75, 100, and 150 mg eq. (which correspond to 39, 78, 117, 156, and 234 mg of paliperidone palmitate) respectively (ie 25‐fold dose conversion factor from oral risperidone to PP1M). Conclusions: This study provides clinicians with a practical guidance to establish suitable maintenance dose levels of PP1M and oral risperidone when transitioning patients from one formulation to another.